PENDEKATAN SAINTIFIK DALAM MENINGKATKAN HASIL BELAJAR PEMBELAJARAN IPA DI KELAS IV SISWA SEKOLAH DASAR - Dina Dahliana; Nike Sri Setiawati; Taufina Taufina (Universitas Syiah Kuala, 2019)
The purpose of this study is to influence the use of a scientific approach to student learning outcomes in science learning in SD Negeri 10 Lambung Bukit, Pauh District, Padang. This research is an experimental research type Quasi Experimental Design with the design of The Static Comparison: Randomized Control Group Only Design. The population in this study were all students in grade IV semester II SD Negeri 10 Lambung Bukit District Pauh which consisted of 2 classes totaling 47 people. Based on the data analysis, the results of testing of the data from the sample class are normally distributed and homogeneous. Furthermore, hypothesis testing was done by t-test showing tcount = 2.464 and ttable = 1.677 with db = 47 (n1 + n2–2 = 24 + 25-2 = 47) and a significant level of 5%. Based on the t-test t table (2,464 1,677) then H0 is rejected and H1 is accepted, with the conclusion that student learning outcomes that use a scientific approach are better than student learning outcomes without using a scientific approach to student learning outcomes in science learning in grade IV elementary school Negeri 10 Lambung Bukit District Pauh.